THE IMPLEMENTATION OF WASTE ALMS FUND MANAGEMENT FROM THE LAZISNU GO TO SCHOOL PROGRAM IN PRAMBON, NGANJUK - Nur Ainia Nofitasari; Fachrial Lailatul Maghfiroh (Al-Muhasib: Journal of Islamic Accounting and Finance, 2024)
Abstract: This study aims to assess the effectiveness of the alms-garbage program and identify the factors that facilitate or hinder its implementation in the LAZISNU Go to School (LGTS) program in the district of Prambon, Nganjuk. The development of human needs is one of the causes of current environmental problems. The amount of domestic, industrial, and transportation waste in rivers, soil, and sea demonstrates this. Therefore, the alms-garbage program serves as a medium to teach students about proper waste management, encouraging them to dispose of waste appropriately and understand that not all waste ends up as dirt. Still, some can be utilized to generate a rupiah, which can then be donated to those in need. This type of research employs a qualitative, case study approach. The subjects in this study were students, school members, LGTS program coordinators, and LAZISNU institutions. This study used participant observation, in-depth interviews, and documentation to collect data. Researchers use data analysis techniques such as data reduction, data presentation, and conclusion drawing. Researchers combine various data collection techniques and existing data sources to validate data. Researchers use source triangulation. The results showed that the evaluation of the alms-garbage program through LGTS, which included putting in place different stages such as introducing the alms-garbage program, getting people to know about the alms-waste program, collecting trash from the waste bank, selling trash, and donating trash, was all successful. The results and benefits of providing waste alms through the LGTS program encompass three aspects: environmental, economic, and social, all of which greatly benefit students and the community who participate in the program. Abstrak: Penelitian ini bertujuan untuk menilai efektivitas program sedekah sampah dan mengidentifikasi faktor-faktor yang memfasilitasi atau menghambat pelaksanaannya dalam program LAZISNU Go to School (LGTS) di Kecamatan Prambon, Kabupaten Nganjuk. Perkembangan kebutuhan manusia menjadi salah satu penyebab permasalahan lingkungan saat ini. Banyaknya sampah domestik, industri, dan transportasi yang ada di sungai, tanah, dan laut menunjukkan hal tersebut. Oleh karena itu, program sedekah sampah ini menjadi media untuk mengajarkan kepada para siswa tentang pengelolaan sampah yang benar, mendorong mereka untuk membuang sampah pada tempatnya dan memahami bahwa tidak semua sampah berakhir sebagai kotoran. Namun, beberapa dapat dimanfaatkan untuk menghasilkan rupiah, yang kemudian dapat disumbangkan kepada mereka yang membutuhkan. Jenis penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Subjek dalam penelitian ini adalah siswa, warga sekolah, koordinator program LGTS, dan lembaga LAZISNU. Penelitian ini menggunakan observasi partisipan, wawancara mendalam, dan dokumentasi untuk mengumpulkan data. Peneliti menggunakan teknik analisis data seperti reduksi data, penyajian data, dan penarikan kesimpulan. Peneliti menggabungkan berbagai teknik pengumpulan data dan sumber data yang telah ada untuk memvalidasi data. Peneliti menggunakan triangulasi sumber. Hasil penelitian menunjukkan bahwa evaluasi program sedekah sampah melalui LGTS yang meliputi berbagai tahapan seperti memperkenalkan program sedekah sampah, mengajak masyarakat untuk mengetahui program sedekah sampah, mengumpulkan sampah dari bank sampah, menjual sampah, dan mendonasikan sampah, semuanya berjalan dengan baik. Hasil dan manfaat sedekah sampah melalui program LGTS mencakup tiga aspek: lingkungan, ekonomi, dan sosial, yang semuanya sangat bermanfaat bagi para siswa dan masyarakat yang berpartisipasi dalam program ini.